Epidemic Outbreak of COVID-19 in Foreign Closed Long-Term Care Facilities - V. G. Akimkin; N. G. Davydova; S. V. Ugleva; Zh. B. Ponezheva; S. V. Shabalina (Эпидемиология и вакцинопрофилактика, 2022)
Objective. Of particular interest is the incidence of COVID-19 in closed groups, in institutions, in particular, in nursing homes, geriatric centers, veterans' homes and neuropsychiatric boarding schools.Methods. Analysis and description of COVID-19 foci in closed long-term care facilities was carried out using literature sources from the MEDLINE medical information database using the PubMed electronic search engine, using the search query CARE HOME OR NURSING HOME OR LONG-TERM CARE FACILITY AND COVID-19 AND OUTBREAK. The share of sick people as a percentage of the total number of residents and individual employees was considered only in those publications that described the outbreak of COVID-19 in a single institution. The absence of data on the number of hospitalizations and deaths, symptoms, and data on the time frame of the outbreak was not an exclusion criterion, but their presence was taken into account in the analysis. We selected mainly publications where people with a positive PCR test for SARS-CoV-2 RNA were considered to be ill with COVID-19. However, it is worth considering that the authors describe outbreaks during the first rise in the incidence of COVID-19 in the world, when there was a shortage of test systems for a new coronavirus infection.Results. An overview of the incidence of COVID-19 in the world in closed long-term care institutions is presented. It has been shown that residents of closed communities are elderly people with many concomitant diseases, in connection with which a severe course of COVID-19 and high mortality are often noted.Conclusion. Convictions about the need to strengthen the quality of anti-epidemic measures in closed long-term care institutions, which are at risk, are summarized.